The Influence of Leadership Style on Employee Loyalty at Karma Kandara - Laksana, Kadek Agung; Sukana Sabudi, I Nyoman; Sihombing, Irene Hanna H. (Jurnal Multidisiplin West Science, 2024)
Lack of leadership style pay attention to the fate of its members can cause low productivity Work. So that leadership style must be able to influence and change the attitudes, and actions of its members for the interests and goals of the organization achieved. Employee loyalty is an important aspect in the success of the organization, because it reflects the level of commitment and attachment of employees to the organization where they work. It happened enhancement amount rotation employees at Karma Kandara for the 2019 - 2023 period which gave rise to desire for researc. The population of this quantitative study is Karma Kandara workers. Up to 71 respondents made up the samples that were used. The study needs certain statistics, specifically the number of employees from year to year. The primary data used in this study are questionnaires, or lists of questions, that were sent to respondents to complete using the Google Form platform. The fed up sample is the retrieval technique sample that is utilized. Utilizing SPSS for Windows version 18, the analysis approach employs basic linear regression. With a significance level of 0.000, it was determined that the leadership style had a tcount value of 5.055> ttable, or 1.7. Given that the significance threshold is less than 0.05, the study's hypothesis supports Ha and rejects Ho. Is it possible to conclude Accepted were the study's findings that "Leadership Style has a positive, direct, and significant effect on Employee Loyalty".